2018
DOI: 10.1017/s0031182018001427
|View full text |Cite
|
Sign up to set email alerts
|

Rodents of Senegal and their role as intermediate hosts of Hydatigera spp. (Cestoda: Taeniidae)

Abstract: Hydatigera (Cestoda: Taeniidae) is a recently resurrected genus including species seldom investigated in sub-Saharan Africa. We surveyed wild small mammal populations in the areas of Richard Toll and Lake Guiers, Senegal, with the objective to evaluate their potential role as intermediate hosts of larval taeniid stages (i.e. metacestodes). Based on genetic sequences of a segment of the mitochondrial DNA gene cytochrome c oxidase subunit 1 (COI), we identified Hydatigera parva metacestodes in 19 out of 172 (11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The H. kamiyai isolates were in a single clade, and the results confirmed that H. kamiyai is genetically distant from H. taeniaeformis s.s. Based on nucleotide sequence comparisons, Catalano et al found that a H. taeniaeformis isolate from a Nile rat (Arvicanthis niloticus) in Senegal showed identity to what was described as H. taeniaeformis s.s., a lineage that might have originated in Southeast Asia and rapidly invaded Australia, the Americas, Europe and Africa, where it has been identified in Ethiopia and South Africa in Rattus spp. (Catalano et al, 2019). Lavikainen et al (2016) has also speculated that H. taeniaeformis probably originated in Asia and has spread worldwide, given its linkage to the Rattini tribe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H. kamiyai isolates were in a single clade, and the results confirmed that H. kamiyai is genetically distant from H. taeniaeformis s.s. Based on nucleotide sequence comparisons, Catalano et al found that a H. taeniaeformis isolate from a Nile rat (Arvicanthis niloticus) in Senegal showed identity to what was described as H. taeniaeformis s.s., a lineage that might have originated in Southeast Asia and rapidly invaded Australia, the Americas, Europe and Africa, where it has been identified in Ethiopia and South Africa in Rattus spp. (Catalano et al, 2019). Lavikainen et al (2016) has also speculated that H. taeniaeformis probably originated in Asia and has spread worldwide, given its linkage to the Rattini tribe.…”
Section: Resultsmentioning
confidence: 99%
“…Some members of the genus Taenia are responsible for taeniasis and/or cysticercosis in humans (Sharma et al, 2016). The resurrection of the genus Hydatigera was proposed in a recent revision of the family Taeniidae; Hydatigera consists of four valid species, Hydatigera taeniaeformis sensu stricto (s.s.), Hydatigera krepkogorski, Hydatigera parva, and Hydatigera kamiyai (Nakao et al, 2013a;Nakao et al, 2013b;Catalano et al, 2019). H. taeniaeformis is found in the small intestine of cats and other felids, which are the definitive hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Each cyst contained one larval stage, which measured from 5 to 130 mm (Figure 1a to c). The cestode specimens showed the diagnostic characteristics of the genus Hydatigera (i. e., large rostellar hooks and metacestodes as strobilocercus with prominent segmented strobilae; Lavikainen et al 2016;Catalano et al 2019). The general characteristics of all strobilocerci found, such as scolex with four suckers of 223 µm length by 120 µm wide; rostellum with double alternative crowns of 17 to 20 hooks each; longer hooks 368 to 409 µm in length and smaller hooks 224 to 246 µm in length (Figures 2, 3), were in accordance with descriptions of H. taeniaeformis given by Dobrovolny and Harbaugh (1934) 1936; Mello et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Natural infections of S. mansoni, S. haematobium, and also notably S. haematobium with S. bovis hybrids, have been observed in some non-human animals such as primates (e.g., baboons), rodents, and pigs [51][52][53][54][55][56][57]. Further, there is also evidence that human S. mansoni is maintained in non-human primates, e.g., in East Africa [57], that shared phylogenetic genotypes are matched, indicative of shared transmission between humans and rodents in West Africa [58].…”
Section: Introductionmentioning
confidence: 99%